2020
DOI: 10.5114/aoms.2019.83644
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal transmission of hepatitis C virus: an update

Abstract: Infection with hepatitis C virus (HCV) is a major health problem worldwide. A large proportion of perinatal HCV infections are silent and may present later in adulthood with long-term complications. HCV has no effective immune prophylaxis and hence appropriate follow-up of all infants born to HCV-infected mothers is necessary. Universal antenatal screening for HCV is largely debatable. Intrauterine and partum transmission of HCV are both possible and higher rates are associated with a high maternal serum viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 125 publications
(166 reference statements)
0
8
1
1
Order By: Relevance
“…For example, if a patient is HCV antibody-positive but demonstrates no viremia, we can counsel that the best evidence suggests that the patient may not transmit HCV infection to their child. Our findings are different from the existing literature 18 in that internal fetal monitoring, prolonged ruptured membranes, and duration of membrane rupture 6 hours longer or did not significantly affect perinatal transmission. We suggest that intrapartum management does not need to be modified in this population, though further research would be necessary to be definitive.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, if a patient is HCV antibody-positive but demonstrates no viremia, we can counsel that the best evidence suggests that the patient may not transmit HCV infection to their child. Our findings are different from the existing literature 18 in that internal fetal monitoring, prolonged ruptured membranes, and duration of membrane rupture 6 hours longer or did not significantly affect perinatal transmission. We suggest that intrapartum management does not need to be modified in this population, though further research would be necessary to be definitive.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the rate of maternal-fetal transmission of HCV varies in different geographical regions. Universal HCV screening during pregnancy is recommended to provide the best pregnancy management interventions to reduce the risk of perinatal HCV transmission [ 10 , 14 ]. The prevalence of HCV in Iran ranges from 0.5% (95% CI: 0.4–0.6%) in blood donors to 0.6% (95% CI: 0.4% to 0.8%) in the general population [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that HCV-infected pregnant women have a 2% to 8% chance of transmitting the virus to their fetus. The process and timing of mother-to-child transmission, however, remain unknown [55]. Some researchers discovered high numbers of NK cells in the placentas of HCV-positive women.…”
Section: Trans-placental Transfer and Vertical Transmission Of Hcvmentioning
confidence: 99%